The effect of vitamin K1 on arterial calcification activity in subjects with diabetes mellitus: a post hoc analysis of a double-blind, randomized, placebo-controlled trial. Issue 1 (12th October 2021) - Bellinge, Jamie W; Francis, Roslyn J; Lee, Sing C; Bondonno, Nicola P; Sim, Marc; Lewis, Joshua R; Watts, Gerald F; Schultz, Carl J
ABSTRACT: Background: Coronary and aortic artery calcifications are generally slow to develop, and their burden predicts cardiovascular disease events. In patients with diabetes mellitus, arterial calcification is accelerated and calcification activity can be detected using 18F-sodium fluoride positron emission tomography (18F-NaF PET). Objectives: We aimed to determine whether vitamin K1 supplementation inhibits arterial calcification activity in individuals with diabetes mellitus. Methods: This was a post hoc analysis of the ViKCoVaC (effect of Vitamin-K1 and Colchicine on Vascular Calcification activity in subjects with Diabetes Mellitus) double-blind randomized controlled trial conducted in Perth, Western Australia. Individuals with diabetes mellitus and established coronary calcification (coronary calcium score > 10), but without clinical coronary artery disease, underwent baseline 18F-NaF PET imaging, followed by oral vitamin K1 supplementation (10 mg/d) or placebo for 3 mo, after which 18F-NaF PET imaging was repeated. We tested whether individuals randomly assigned to vitamin K1 supplementation had reduced development of new 18F-NaF PET positive lesions within the coronary arteries and aorta. Results: In total, 149 individuals completed baseline and follow-up imaging studies. Vitamin K1 supplementation independently decreased the odds of developing new 18F-NaF PET positive lesions in the coronary arteries (OR: 0.35; 95% CI: 0.16, 0.78; P  = 0.010), aorta (OR: 0.27; 95% CI: 0.08, 0.94; P  = 0.040), and in both aortic and coronary arteries (OR: 0.28; 95% CI: 0.13, 0.63; P  = 0.002). Conclusions: In individuals with diabetes mellitus, supplementation with 10 mg vitamin K1 /d may prevent the development of newly calcifying lesions within the aorta and the coronary arteries as detected using 18F-NaF PET. Further long-term studies are needed to test this hypothesis. This trial was registered at anzctr.org.au as ACTRN12616000024448.